Toponymy on the periphery : placenames of the Eastern Desert, Red Sea, and south Sinai in Egyptian documents from the early dynastic until the end of the New Kingdom - Cooper, Julien Charles, (Probleme der Ägyptologie;, 2020)
"In Toponymy on the Periphery, Julien Charles Cooper conducts a study of the rich geographies preserved in Egyptian texts relating to the desert regions east of Egypt. These regions, filled with mines, quarries, nomadic camps, and harbours are often considered as an unimportant hinterland of the Egyptian state, but this work reveals the wide explorations and awareness Egyptians had of the Red Sea and its adjacent deserts, from the Sinai in the north to Punt in the south. The book attempts to locate many of the placenames present in Egyptian texts and analyse their etymology in light of Egyptian linguistics and the various foreign languages spoken in the adjacent deserts and distant shores of the Red Sea".